2017
DOI: 10.1088/1748-9326/aa869e
|View full text |Cite
|
Sign up to set email alerts
|

Identification of deficiencies in seasonal rainfall simulated by CMIP5 climate models

Abstract: An objective technique for analysing seasonality, in terms of regime, progression and timing of the wet seasons, is applied in the evaluation of CMIP5 simulations across continental Africa. Atmosphere-only and coupled integrations capture the gross observed patterns of seasonal progression and give mean onset/cessation dates within 18 days of the observational dates for 11 of the 13 regions considered. Accurate representation of seasonality over central-southern Africa and West Africa (excluding the southern c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 69 publications
6
28
0
Order By: Relevance
“…Some of the characteristics of these regional differences and those between the AMIP and coupled ensembles are also present in studies of East Africa, mostly revolving around model representation of the onset rainy season (AM or MAM). For instance, Rowell et al (2015) showed that coupled CMIP5 have more trouble reproducing trends in this season than AMIP models, while Dunning et al (2017) showed that CMIP5 models simulate late onset in this season. For this reason the transitions from the biases in the Awash basin to the biases in Northwest Ethiopia have proved interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the characteristics of these regional differences and those between the AMIP and coupled ensembles are also present in studies of East Africa, mostly revolving around model representation of the onset rainy season (AM or MAM). For instance, Rowell et al (2015) showed that coupled CMIP5 have more trouble reproducing trends in this season than AMIP models, while Dunning et al (2017) showed that CMIP5 models simulate late onset in this season. For this reason the transitions from the biases in the Awash basin to the biases in Northwest Ethiopia have proved interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Onset and cessation dates were calculated using the methodology of Dunning et al (2016), which extends the methodology of Liebmann et al (2012). For analysis of changes in onset and cessation dates the method is applied separately to the three time periods used (recent period, mid-twenty-first century, and end of the twentyfirst century).…”
Section: B Methodology For Identifying Onset and Cessation Of Rainfamentioning
confidence: 99%
“…The method has three stages; full details of the method can be found in Dunning et al (2016). First, the seasonal regime at each grid point is categorized as being a dominantly annual regime (one wet season per year) or biannual regime (two wet seasons per year).…”
Section: B Methodology For Identifying Onset and Cessation Of Rainfamentioning
confidence: 99%
See 1 more Smart Citation
“…Precipitation over southern West Africa (SWA) is important for agriculture and water resources, yet model simulations of precipitation amount and variability are uncertain over the region (e.g. Cook and Vizy, 2006;Roehrig et al, 2013;Vellinga et al, 2013;Dunning et al, 2017). Accurate observations of precipitation are therefore crucial for understanding the processes responsible for the model discrepancies.…”
Section: Introductionmentioning
confidence: 99%